Impact of Obesity on Drug Survival of Tofacitinib in Patients with Rheumatoid Arthritis: Analysis from the Turkbio Registry - Babaoglu, Hakan; Goker, Borna; Inanc, Nevsun; Birlik, Merih; Koca, Suleyman Serdar; Cefle, Ayse; Gazel, Ummugulsum (Wiley, 2018)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-for-Rheumatology-Health-Professionals (ARHP) -- OCT 19-24, 2018 -- Chicago, IL